THE BARRIER ROLE OF MACROPHYTES IN POLLUTION OF WATER BODIES WITH MICRIPLASTICS - V. D. Kazmiruk (Наука. Инновации. Технологии)
Introduction. The widespread use of plastic products, both for industrial and household needs, the relative cheapness, ease of production and processing of plastics, the ability to change their physical and consumer properties, led to the fact that this material has become one of the most popular in the life of modern society. At the same time, the massive use of synthetic polymer materials has given rise to the emergence of a new environmental pollutant - plastic microparticles (microplastics). It has been experimentally established that, aquatic plants make it possible to localize waters pollution by microplastics and contribute to its deposition and burial. Materials and methods of research. Field and laboratory studies was conducted to envestigate the retention rate of high-density polyethylene microparticles by Phragmites communis Trin., Typha angustifolia L., Glyceria maxima, Acorus calamus L., Iris pseudacorus, Carex acuta, Ceratophyllum demersum L. Potamogeton perfoliatus L., Potamogeton lucens L., Potamogeton natans, P. hetero-phyllus x P. Perfoliatus, Nymphaea candida, Nuphar lutea (L.) Smith, and Trapa natans. It has been experimentally established that, the retention rate of plastic microparticles by macrophytes depends on the material of their origin, particle hardness, size, concentration, as well as density, morphological and ecological characteristics of plants. For various species of macrophytes, the retention rate of microparticles in the size range of 1-5 mm ranges from 22 to 100 %>. The obtained results showed a good agreement with the materials of recent studies on the interaction between plastic microparticles with macrophytes of marine regions. Results and Discussion. Conclusion. The regulation of surface water pollution by microparticles of synthetic polymeric materials, along with other measures, can include targeted cultivation of aquatic plants, their introduction and biomass growth at the right time, in the right places and in the required quantities. Such zones can function autonomously without human intervention and capital investments. For the placement and creation of buffer zones with macrophytes, it is possible to use lands that are not suitable for other uses - former landfills, wastelands, small dry valleys, wetlands.